2023
DOI: 10.3390/ijerph20064776
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Scans of Full Dental Arches: An In Vitro Measurement Study of the Accuracy of Different Intraoral Scanners

Abstract: The aim of this in vitro study was to evaluate the accuracy of different intraoral scanners (IOS), according to different scanning strategies and to the experience of the operator. Six IOS setups were used in this study. Ten scans of a complete epoxy-resin-made maxillary dental arch were performed with each IOS, using four different scanning techniques (manufacturer-suggested scanning strategy, cut-out rescan technique, simplified scanning technique, novel scanning technique). Scans were also performed by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…When scanning the maxilla, starting from the occlusal to the buccal to the palatal surface is recommended, and when scanning the mandible, from the occlusal to the lingual to the buccal surface is preferred [ 36 – 39 ]. In the case of Medit IOS, the recommended scanning strategy starts at the occlusal surface (in both upper and lower jaws), and then the scanning should be continued on the oral surface and finally the vestibular side [ 40 ]. Using the Planmeca Emerald IOS, the scanning strategy is as follows (both in maxilla and mandible): the scanning starts on the occlusal surface from the molar region until the middle of the arch, after that the oral and then the vestibular surface is scanned.…”
Section: Methodsmentioning
confidence: 99%
“…When scanning the maxilla, starting from the occlusal to the buccal to the palatal surface is recommended, and when scanning the mandible, from the occlusal to the lingual to the buccal surface is preferred [ 36 – 39 ]. In the case of Medit IOS, the recommended scanning strategy starts at the occlusal surface (in both upper and lower jaws), and then the scanning should be continued on the oral surface and finally the vestibular side [ 40 ]. Using the Planmeca Emerald IOS, the scanning strategy is as follows (both in maxilla and mandible): the scanning starts on the occlusal surface from the molar region until the middle of the arch, after that the oral and then the vestibular surface is scanned.…”
Section: Methodsmentioning
confidence: 99%
“…Different types of intraoral scanners are available, like the iTERO Element 5D plus, CEREC Primescan, Medit 1700, Omnicam, Dexis IS 3700, Trios 3, and 3Shape Trios 5 Wireless [ 40 , 41 , 42 , 43 ]. Overall, the highest precision outcomes were seen with iTero5D, Medit i700, and Omnicam [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of intraoral scanners are available, like the iTERO Element 5D plus, CEREC Primescan, Medit 1700, Omnicam, Dexis IS 3700, Trios 3, and 3Shape Trios 5 Wireless [ 40 , 41 , 42 , 43 ]. Overall, the highest precision outcomes were seen with iTero5D, Medit i700, and Omnicam [ 40 ]. In another study, the authors reported that deviations in trueness and precision between these scanners would not be clinically relevant since the recorded accuracy values were of clinical acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Bu gelişmeler AİT'lerin konvansiyonel ölçüler kadar hassas olmasını sağlamıştır. 7 Dijital ağız içi tarama, yüksek hasta memnuniyeti, basitleştirilmiş üretim prosedürü ve maliyetlerdeki düşüş nedeniyle diş hekimliğinde popülerlik kazanmaktadır. 8,9 AİT'ler optik ölçü almak için kullanılırlar ve bir ışık demeti kullanarak diş arkının şekli/boyutu ve implantların konumu hakkında bilgi toplamaktadırlar.…”
Section: Introductionunclassified
“…30 AİT'lerin performanslarının, ağız içi ortamın değişkenlerini de taklit eden çalışmalarla değerlendirilmesi, bu cihazların potansiyel faydalarını ve sınırlılıklarını belirlememize yardımcı olacaktır. 7 Ayrıca, daha geniş bir tarayıcı yelpazesini içeren ve farklı ölçüm yöntemlerini inceleyen çalışmalar AİT'lerin etkili şekilde kullanmamızı sağlamaya yardımcı olabilir. Bu nedenle AİT'lerin dental implantların ölçüm hassasiyetlerinin incelenmesi için farklı marka cihazlar, implant sayısının artırılması ve implant açıları gibi faktörlerin de planlamaya katıldığı daha detaylı araştırmalara ihtiyaç duyulmaktadır.…”
Section: Introductionunclassified